Atitudes dos docentes da educação básica perante as avaliações externas aplicadas em larga escala: a realidade do contexto capixaba - Prado, Wallacy Campos (2023)
The aim of this study was to analyze the attitudes of teachers in the public education system of the state of Espírito Santo towards large-scale external assessments. The study aimed to answer this key question: How do teachers in this network see, feel and behave in relation to large-scale external assessments, and how are these attitudes related to their working conditions? In order to achieve this, the general objective was to analyze the attitudes of primary school teachers towards large-scale external assessments in the context of the state of Espírito Santo. Concerning epistemological perspective this investigation assumed the theory of attitudes, proposed by Eagly and Chaiken's (1993), associated with the classic tricomponent theory of attitudes by Rosenberg and Hovland (1960). Methodologically a qualitative-quantitative, quantitative and non-experimental approach was applied using an instrumental framework (Carretero-Dios & Pérez, 2007), using a cross-sectional design in which the Attitudes Toward Large-Scale External Assessments Scale was administered to 405 teachers from the State Department of Education. Scale scores were analysed using descriptive statistics, including mean, standard deviation and coefficient of variation. Additionally, inferential analyses were conducted to examine the proposed hypotheses and to investigate the relationship between teachers' attitudes and working conditions. The findings reveal the evaluative nature of the state, characterized by a comprehensive assessment agenda that has had a significant impact on classroom practice, particularly within the context of state policies that hold education professionals accountable. Significant differences in attitude were found between fixed-term and permanent teachers and between teachers from different fields of knowledge, while no significant differences were found in workload. In addition, an analysis aligned with legislation revealed discrepancies in teachers' perceptions, indicating different approaches to evaluation and highlighting the need to restructure evaluation policies in the state of Espírito Santo.